The B Fields in OB Stars (BOB) Survey. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Morel, T.; Castro, N.; Fossati, L.; Hubrig, S.; Langer, N.; Przybilla, N.; Schöller, M.; Carroll, T.; Ilyin, I.; Irrgang, A.; Oskinova, L.; Schneider, F. R. N.; et al.
Abstract: The B fields in OB stars (BOB) survey is an ESO large programme collecting spectropolarimetric observations for a large number of early-type stars in order to study the occurrence rate, properties, and ultimately the origin of magnetic fields in massive stars. As of July 2014, a total of 98 objects were observed over 20 nights with FORS2 and HARPSpol. Our preliminary results indicate that the fraction of magnetic OB stars with an organised, detectable field is low. This conclusion, now independently reached by two different surveys, has profound implications for any theoretical model attempting to explain the field formation in these objects. We discuss in this contribution some important issues addressed by our observations (e.g., the lower bound of the field strength) and the discovery of some remarkable objects.